ISLAM, NEGARA, DAN PERLINDUNGAN HAK-HAK ISLAM MINORITAS - Ahmad Solikhin (Journal of Governance, 2016)
Abstract: This paper discusses the loss of the State's role in upholding the freedom of minority political Islamic groups in Indonesia. Political freedom that guaranteed by the Constitution for every citizen is dominated by Islamist groups majority. They tend to create policies that discriminate minority of Islamic group. As a result Islamic group minority do not get their political rights as citizens of Indonesia that had the principle of "Unity in Diversity." Keywords: Country, Religion, Islam Minority Rights